The factorial productivity components of peas with leafless and leafy morphotypes - I. A. Filatova (Зерновое хозяйство России, 2020)
The research work was carried out in the conditions of the southeast of the Voronezh region in the fields of the Research Institute of Agriculture of the Central-Blackearth area named after V. V. Dokuchaev in 2015-2017. The weather conditions during the years of the trial were quite favorable. The water and thermal regimes provided optimal conditions for the growth and development of pea plants, 1.3 in 2015, 1.2 in 2016 and 1.1 in 2017. The purpose of the study was to identify the factorial components that determine the productivity of peas belonging to different morphotypes. There were selected highly productive lines as objects of study. Before harvesting there was selected a material for analysis, and there were determined the following indicators: plant height, number of productive nodes, number of beans per plant, number of grains in a bean, number of grains per plant, 1000 grains weight, grain weight per plant. The grain productivity was determined after harvesting with a combine in terms of 14% moisture content. As a result of the analysis, there was found that the formation of grain productivity in peas of a leafy morphotype in comparison with a leafless morphotype was provided by a greater number of fruiting nodes: 3.31 and 2.53 pcs/plant. respectively (+0.78 pcs/plant); beans per plant: 5.27 and 4.19 pcs/plant. (+1.08 pcs/plant); and grains per plant: 18.6 and 17.5 pcs/plant (+1.1 pcs/plant). The productivity of the samples with a leafless morphotype was due to a larger number of grains per bean: 4.24 and 3.61 pieces/bean (+0.63 pieces/ bean) and heavier grains: 236 and 228 g (1000 grain weight +8 d). Differences in the trait “number of grains per plant” and “1000 grain weight” were within the experimental error.